Penile Skin as a Rare Location of Melanoma in the Balkan Region: A Case Report - Gacic, Jasna (2025)
Skin melanoma is very rarely found in the genital region. Additionally, out of all penile skin malignancies, melanoma is one of the rarest, with no cases reported before in the Balkan region. A 68-year-old male presented with atypical and irregular pigmented skin lesions on his left flank and penile shaft. After dermoscopy and radiological work-up, both lesions were completely excised, with pathological examination revealing a high-grade dysplastic nevus with nodular melanoma in the penile location. Wide re-excision was performed one month later, followed by skin reconstruction with a rotation cutaneous flap. No postoperative complications, long-term recurrence signs, nor local or distant metastases were observed. As a very rare case of this kind of condition in the Balkan region and globally, this is the first case of penile skin melanoma described in Serbia, additionally emphasizing the importance of thorough systematic clinical examination and conducting organ-preserving surgery.